PENGARUH NON-PERFORMING LOAN, ‘LOAN TO DEPOSIT RATIO’, NET INTEREST MARGIN, ‘CAPITAL ADEQUACY RATIO’ TERHADAP PROFITABILITAS” - Mahendra Giri, I Gede Taksu; Purbawangsa, Ida Bagus Anom (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.08.TAHUN.2022DO - 10.24843/EEB.2022.v11.i08.p02, 2022)
The purpose of this study was to determine the effect of non-performing loan (NPL), loan to deposit ratio (LDR), net interest margin (NIM) and capital adequacy ratio (CAR) simultaneously and partially on the profitability of PT. Pedungan Rural Bank. This study uses quantitative research, namely by looking at the financial statements of the I-IV quarters for the 2014-2019 period. The sampling technique used was purposive sampling technique. The data analysis technique used in this research is multiple linear regression analysis technique. It was found that simultaneously the variables of Non-Performing Loan (NPL), Loan to Deposit Ratio (LDR), Net Interest Margin (NIM), Capital Adequacy Ratio (CAR) had an effect on profitability. Partially, Non-Performing Loan (NPL) has a negative and significant effect on profitability. Loan to Deposit Ratio (LDR) has a positive and significant effect on profitability. Net Interest Margin (NIM) has a positive and significant effect on profitability. Capital Adequacy Ratio (CAR) has a positive and significant effect on profitability.